Development of E-Learning Media Based on Google Sites LMS in Social Studies Learning Class V - Prayogi, Helmy (International Journal for Educational and Vocational Studies)
Background: Mastery of technology is an obstacle for teachers in implementing learning during the Covid-19 pandemic, especially in disadvantaged areas. Offline learning makes teachers easily bored and has difficulty designing creative, effective and efficient learning. Likewise with students, if the learning methods and media are monotonous, the process of understanding the material will be difficult and less than optimal. This study aims to determine the level of validity and practicality and to produce E-Learning media based on the LMS Google Sites Materials on Socio-Cultural Diversity in Indonesia Class V at Labschool UNESA 2 Elementary School. This research is Research and Development with a quantitative research type. Study carried out at Labschool UNESA 2 Elementary School with a sample of 33 students and 2 validators (media experts and material experts). Technical data collection using interviews and questionnaires. The results of this study indicate that the level of validity of the E-Learning media based on Google Sites learning management system (LMS) from material experts and media experts respectively obtained a percentage of 93.75% "very valid" and 72.75% "valid". Meanwhile, from the practicality test by teachers, 92% "very practical" and 98% students "very practical". E-Learning media based on Google Sites LMS and as an alternative learning media on Socio-Cultural Diversity in Indonesia for grade V Elementary School can be declared feasible and practical. E-Learning media based on Google Sites LMS and as an alternative learning media on Socio-Cultural Diversity in Indonesia grade V Elementary School can be declared feasible and practical.